Basilar Artery Lateral Displacement May Be Associated with Migraine with Aura - Zhang, Cen; Detre, John A.; Kasner, Scott E.; Cucchiara, Brett (Frontiers in Neurology, 2018)
Abstract: OBJECTIVE To determine if structural features of the vertebrobasilar arterial system are related to migraine. BACKGROUND Alterations in cerebral vascular structure and function have been associated with migraine, possibly mediated by hypoperfusion and/or endothelial dysfunction triggering cortical spreading depression. Vessel tortuosity, in particular, has been associated with both altered hemodynamics and endothelial function. Symptoms of migraine with aura often localize to the occipital cortex, and evidence supports the localization of a migraine generator to the brainstem, suggesting that the vertebrobasilar system may be of particular relevance. METHODS We performed a post-hoc exploratory analysis of data collected in a prospective, observational, case-control study enrolling migraine with aura (MWA), migraine without aura (MwoA), and control subjects in a 1:1:1 ratio. 3T high-resolution MR angiography was used to assess vascular structure, and arterial spin labeled perfusion MRI to measure interictal cerebral blood flow (CBF). White matter lesions were assessed using T2/FLAIR. Vertebral and basilar artery (BA) diameters and BA total lateral displacement were measured. RESULTS 162 subjects were included (52 control/52 MWA/ 58 MwoA). Mean age was 33 ± 6 years, and 78% were female. BA diameter was similar across groups (3.6 ± 0.6 mm in all 3 groups). BA displacement was similar in MwoA (5.1±3.0 mm) and controls (4.9±3.1 mm), but tended to be greater in MWA (6.3±3.8 mm, p=0.055 vs. controls). BA displacement increased with age (p<0.001) was greater in men vs. women (6.6±4.2 vs. 5.1±3.0, p=0.02) and with increased migraine frequency (p=0.03). In multivariate analysis, BA displacement was significantly greater in MWA subjects (p=0.02), with older age (p=0.003), and in men (p=0.046). In regression analysis adjusted for age and sex, BA displacement remained significantly greater with increasing migraine frequency (p=0.02). There was no association between BA displacement and interictal posterior cerebral artery territory CBF or overall white matter lesions. CONCLUSIONS Basilar artery lateral displacement may be associated with MWA as well as headache frequency. This association does not appear to be mediated by cerebral hypoperfusion.